PENGARUH KENAIKAN PAJAK PERTAMBAHAN NILAI (PPN) TERHADAP PENDAPATAN WAJIB PAJAK BADAN USAHA DI KOTA METRO - yudistira, era (Akuntabilitas, 2023)
One of the efforts to restore state budget conditions carried out by the government is to increase the rate of value added tax (VAT) to 11% under the Law on Harmonization of Tax Regulations Number 7 of 2021. With this increase in VAT, it will certainly have an impact on increasing costs in the producer sector for later passed on by small and medium enterprises (SMEs) to consumers through rising product prices. With the increase in VAT, it will certainly have an impact on increasing costs in the producer sector, which will then be passed on by micro, small and medium enterprises (MSMEs) to consumers through rising product prices.The purpose of this study is to determine whether there is an effect of an increase in Value Added Tax (VAT) on the income of business entity taxpayers in the Metro City Tax Service Office (KPP). Data analysis used was descriptive statistical test, instrument validity test, instrument reliability test, prerequisite test, simple regression analysis, t test, and the coefficient of determination (R2). The results showed that the increase in the 11% VAT rate had a negative effect on business income in Metro City.Keywords: 11% VAT, business income, SMEs